Efektivitas Sumber Daya Kompi Pelopor Khusus Satuan Iii Pelopor pada Operasi Camar Maleo 2015 dalam Penanganan Terorisme di Poso Sulawesi Tengah - Riki Donaire Piliang (Airlangga Development Journal, 2020)
This research is motivated by the problem of resource management during the Police Operation by the Special Pioneer Company in handling terrorism in Poso, Central Sulawesi. This resource management covers human resources, facilities and infrastructure as well as the budget given to prepare and carry out the operations of the 2015 Seagull Police Operations. This is so that the implementation of the tasks of members is ready and reduces the risks and obstacles that occur. In human resources, the goal to be achieved is how to prepare qualified and healthy personnel, while the facilities and infrastructure as a tool to support how the implementation of tasks can run well because of the support of equipment and equipment that can facilitate members in achieving organizational goals. While the budget is a fund that is used to meet the needs in economic aspects as well as to provide goods by buying the goods needed. This study uses a qualitative method because according to the author this method is most appropriate for finding the facts in the field and for exploring more about the results obtained from the facts in the field. The subjects of this study were all members of Pamen, Pama, Bintara and Tamtama who were members of the 2015 Seagull Operation in Poso, Central Sulawesi. Data collection techniques used by the author include interviews, document completions and documentation in the process before, during and after carrying out the task. The results of research in human resources there are still personnel who do not comply with the guidelines or criteria needed by members so that there are still constraints in human resources, in facilities and infrastructure there are obstacles regarding accommodation, equipment and equipment that are not available up to the facilities and infrastructure that are needed it is not in accordance with its function, whereas in the budget the lack of or slow budget given and the source of the budget that is not appropriate is ineffective in the sub-section of the budget in the 2015 Seagull Operations by the Special Pioneer Group III Pioneer Company. Therefore, it is expected that in other future Police Operations it must be more focused and ready in the management of task resources so that what becomes an obstacle can be better addressed by maximizing the management of resources for successful and effective organizational goals.